VHDL modelling of the open short tester - Pang, W. L.; Chew, K. W.; Choong, Florence; Chan, C. L. (2007)
IC (Integrated Circuitry) testing requires the very advanced and sophisticated Advance Test Equipment (ATE) that costs multi million USD. The cost of IC testing is increasing yearly and it will exceed the cost of manufacturing in future. The manufacturers are interested to lower down the manufacturing cost. Low cost tester is one of the options to reduce the manufacturing cost. The low cost FPGA realization of Open/Short Test on IC is introduced to reduce the IC test cost. The open short test is selected, because it is the first IC test. The Very High Speed Integrated Circuit Hardware Description Language (VHDL) is used to model the Open/Short Test on IC and the design is capable to perform the open/short test.